The Use of Artificial Intelligence (AI) Tools to Enhance University Students’ Academic Writing Skills in English Education - Sanzain, Sofia Dwi; Ilham, Ilham; Rahmaniah, Rima (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The rapid advancement of technology has transformed higher education, particularly in the domain of English academic writing, which requires complex cognitive, linguistic, and organizational skills. This study investigates the effectiveness of Artificial Intelligence (AI) tools in enhancing university students’ academic writing performance, cognitive engagement, and learner autonomy. Using a quantitative one-group pretest–posttest design, 20 students participated in an AI-assisted writing intervention incorporating grammar checkers, paraphrasing aids, vocabulary enhancers, and automated feedback. Descriptive and non-parametric analyses, including the Wilcoxon Signed-Rank Test, were conducted to evaluate changes in writing performance, while students’ perceptions were collected via questionnaires. The findings indicate significant improvements in accuracy, coherence, and overall writing quality, with reduced performance gaps among students. Learners reported positive experiences, emphasizing increased confidence, motivation, and autonomy in the writing process. Despite methodological limitations, the results highlight the pedagogical and cognitive benefits of AI integration, suggesting that AI tools can function as effective scaffolds for complex writing tasks. Implications for curriculum design and future research on long-term and diverse applications are also discussed.